Into the bloom: Molecular response of pelagic tunicates to fluctuating food availability. Issue 2 (18th December 2019) - Sordino, Paolo; D'Aniello, Salvatore; Pelletier, Eric; Wincker, Patrick; Nittoli, Valeria; Stemmann, Lars; Mazzocchi, Maria Grazia; Lombard, Fabien; Iudicone, Daniele; Caputi, Luigi
Abstract: The planktonic tunicates appendicularians and thaliaceans are highly efficient filter feeders on a wide range of prey size including bacteria and have shorter generation times than any other marine grazers. These traits allow some tunicate species to reach high population densities and ensure their success in a favourable environment. However, there are still few studies focusing on which genes and gene pathways are associated with responses of pelagic tunicates to environmental variability. Herein, we present the effect of food availability increase on tunicate community and gene expression at the Marquesas Islands (South‐East Pacific Ocean). By using data from the Tara Oceans expedition, we show that changes in phytoplankton density and composition trigger the success of a dominant larvacean species (an undescribed appendicularian). Transcriptional signature to the autotroph bloom suggests key functions in specific physiological processes, i.e., energy metabolism, muscle contraction, membrane trafficking, and proteostasis. The relative abundance of reverse transcription‐related Pfams was lower at bloom conditions, suggesting a link with adaptive genetic diversity in tunicates in natural ecosystems. Downstream of the bloom, pelagic tunicates were outcompeted by copepods. Our work represents the first metaomics study of the biological effects of phytoplankton bloom on a key zooplankton taxon.